A Computer Experiment in the Auditing Class. - Myers, John H.; Kinney, James R. (The Accounting Review, 1972)
This article presents information on the undergraduate auditing course at Indiana University. One of the departures is in the computer work, which is included. The School of Business has instituted a new required computer course for sophomores, but the problem orientation of the experience is likely to remain predominant In the auditing course. In an effort to make the computer lecture material meaningful to the students, a data processing computer problem was developed and used this past semester. The computer problem is used as an aid in teaching data processing controls, test decks and flowcharting. The problem employs a payroll processing routine to illustrate the various types of controls. The payroll example was selected because most of the students are familiar with computerized payroll checks and the program offers the student personalized feedback in the form of a simulated paycheck. The feedback feature encourages the students to try to "beat the system," and in so doing explore the controls built into the program.